2018
DOI: 10.7752/jpes.2018.03254
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Purpose: The aim of the present study was to investigate the coaches' point of view on the rhythmic gymnasts' disordered eating behaviors, by focusing the attention on their knowledge of this problem, in relation to training and competition participation. The second aim is to assess if there is theoretical and/or practical collaboration between coaches and medical staff. Methods: One hundred and Sixty-nine rhythmic gymnastics coaches completed a 23 items questionnaire, based on the NCAA survey (National Colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…The use of WPS-F questionnaire in Greek sport populations' studies will offer important information that sport psychologists can use in educational and prevention programs addressed to coaches and other individuals in the sports environment (e.g., judges). As coaches seem to have one of the most important roles in an athlete's life and, specifically, regarding the pressures about weight and shape (Anderson et al, 2012;Ceballos et al, 2019;Coker-Cranney & Reel, 2015;di Cagno et al, 2018;Voelker et al, 2022), their education and improved information should be a priority. After all, studies have shown that a relationship between coach and athlete that is characterized by communication, empathy, and trust can protect against eating pathology (de Bruin & Oudejans, 2018;Francisco et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The use of WPS-F questionnaire in Greek sport populations' studies will offer important information that sport psychologists can use in educational and prevention programs addressed to coaches and other individuals in the sports environment (e.g., judges). As coaches seem to have one of the most important roles in an athlete's life and, specifically, regarding the pressures about weight and shape (Anderson et al, 2012;Ceballos et al, 2019;Coker-Cranney & Reel, 2015;di Cagno et al, 2018;Voelker et al, 2022), their education and improved information should be a priority. After all, studies have shown that a relationship between coach and athlete that is characterized by communication, empathy, and trust can protect against eating pathology (de Bruin & Oudejans, 2018;Francisco et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Beberapa studi menjelaskan faktor performa senam ritmik melalui perspektif keseluruhan dimana saling terkait antara latihan dan performa (Utami, Kartika, Damayanti, & Nugroho, 2004;Di Cagno et al 2018;Fernández-Villarino et al 2018), dan penelitian lain menjelaskan beberapa faktor prediksi seperti karakteristik antopometri, kondisi fisik atau aspek teknis dari performa secara terpisah (Miletić, Katić, & Males, 2004 Baharun, 2016) menyatakan bahwa agar mendapatkan pengalaman gerak yang baik pada anak-anak maka dalam mendidik anak usia dini harus memperhatikan pembelajaran gerak. Hughes (2009) menyatakan komponen yang sangat esensial untuk pemahaman tentang pengetahuan atau kognitif adalah aktivitas fisik.…”
Section: Pendahuluanunclassified